A Case for Microtubule Vulnerability in Amyotrophic Lateral Sclerosis: Altered Dynamics During Disease - Clark, Jayden A. (Front Cell Neurosci, 2016)
Amyotrophic lateral sclerosis (ALS) is an aggressive multifactorial disease converging on a common pathology: the degeneration of motor neurons (MNs), their axons and neuromuscular synapses. This vulnerability and dysfunction of MNs highlights the dependency of these large cells on their intracellular machinery. Neuronal microtubules (MTs) are intracellular structures that facilitate a myriad of vital neuronal functions, including activity dependent axonal transport. In ALS, it is becoming increasingly apparent that MTs are likely to be a critical component of this disease. Not only are disruptions in this intracellular machinery present in the vast majority of seemingly sporadic cases, recent research has revealed that mutation to a microtubule protein, the tubulin isoform TUBA4A, is sufficient to cause a familial, albeit rare, form of disease. In both sporadic and familial disease, studies have provided evidence that microtubule mediated deficits in axonal transport are the tipping point for MN survivability. Axonal transport deficits would lead to abnormal mitochondrial recycling, decreased vesicle and mRNA transport and limited signaling of key survival factors from the neurons peripheral synapses, causing the characteristic peripheral “die back”. This disruption to microtubule dependant transport in ALS has been shown to result from alterations in the phenomenon of microtubule dynamic instability: the rapid growth and shrinkage of microtubule polymers. This is accomplished primarily due to aberrant alterations to microtubule associated proteins (MAPs) that regulate microtubule stability. Indeed, the current literature would argue that microtubule stability, particularly alterations in their dynamics, may be the initial driving force behind many familial and sporadic insults in ALS. Pharmacological stabilization of the microtubule network offers an attractive therapeutic strategy in ALS; indeed it has shown promise in many neurological disorders, ALS included. However, the pathophysiological involvement of MTs and their functions is still poorly understood in ALS. Future investigations will hopefully uncover further therapeutic targets that may aid in combating this awful disease.